Representasi Kecantikan Rambut Perempuan Dalam Iklan YouTube Dove Indonesia Versi â€œRambutku Mahkotakuâ€ - Rahma Ismianti; Aminah Swarnawati (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Women often lose confidence in their appearance. Dove Indonesia, through the "My Hair My Crown" version of the advertisement on YouTube, seeks to support women to be confident by recounting experiences of hair bullying in the form of negative comments. The aim of the research is to understand the construction of social reality and reveal meaning in advertising using Charles Sanders Peirce's semiotics analysis. The method used is content analysis of advertising texts with the unit of analysis in the form of scenes that refer to the research object. The results of the research show that the construction in the Dove Indonesia YouTube advertisement version "my hair is my crown" is contrary to advertisements in general, in this advertisement women are depicted as having self-esteem and confidence in the beauty of their diverse hair by expressing the meaning that the diversity of women's hair will slowly shift the concept beautiful on ideal hair. The existence of advertisements like this will be persuasive and encourage people, especially women, to be themselves and not force themselves to achieve beauty standards. So advertisements in Indonesia must highlight subjective beauty through visual images and the messages conveyed.